2012
DOI: 10.3892/ijo.2012.1384
|View full text |Cite
|
Sign up to set email alerts
|

Progestin therapy for endometrial cancer: The potential of fourth-generation progestin (Review)

Abstract: Abstract. Progestin preparations are made of synthetic progesterone and have often been used for hormone therapy in gynecological patients with endometriosis or endometrial cancer. Hormone therapy using progestin is considered to be one of the effective means of treatment particularly when dealing with endometrial cancer (an estrogen-dependent tumor). Numerous reports have been published concerning its efficacy in advanced or recurrent cases of atypical endometrial hyperplasia or endometrial cancer. Dienogest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…Women with pre-invasive atypical hyperplasia or early stages of endometrial cancers without myometrial invasion showed high response rates (70–90%) to progestin treatment [46]. The advanced stage or recurrent cancers are 20–30% responsive to progestins [47, 48]. Progestin preparations are used effectively to treat endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Women with pre-invasive atypical hyperplasia or early stages of endometrial cancers without myometrial invasion showed high response rates (70–90%) to progestin treatment [46]. The advanced stage or recurrent cancers are 20–30% responsive to progestins [47, 48]. Progestin preparations are used effectively to treat endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DIE, a fourth-generation progestin, was used in a contraceptive pill and in hormone replacement therapy [14]. Sasagawa et al [10] mentioned that DIE had a good specificity to progesterone receptor compared to other progestins.…”
Section: Discussionmentioning
confidence: 99%
“…High response rates (70-90%) are often observed for women with pre-invasive atypical hyperplasia or early stages of endometrial cancers without myometrial invasion (Kaku, et al 2001; Ushijima, et al 2007). Yet, the efficacy of progestins declines to modest response rates (15-25%) when used for cases of advanced or recurrent cancer (Banno, et al 2012) and more than 30% of patients with well-differentiated, hormone-dependent Type I tumors will fail to respond (Shao 2013). The mechanisms that result in the progression from progestin sensitivity to the hormone refractory state, or “progesterone resistance”, are poorly understood.…”
Section: Uterusmentioning
confidence: 99%